The Effect of Visual and Auditory Information on Illness Perceptions and Patient Satisfaction in Knee Osteoarthritis - Karabaş, Çağlar; Çalış, Havva Talay; Kutluca, Abdurrahman; Topaloğlu, Ulaş Serkan (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2021)
Aim To evaluate the effect of visual and auditory information about knee osteoarthritis on illness perception and patient satisfaction with electronic guidance.Method In this randomized controlled and single-blind study, 100 patients with osteoarthritis were included in two groups (50 video group, 50 control group). The video group was informed about knee osteoarthritis by a physician and then watched a video. The control group was only informed about knee osteoarthritis by the same physician. Before and after the information, Visual Analog Scale, a Likert scale for patient satisfaction, and the Brief Illness Perception Questionnaire (B-IPQ) were filled.Results In the analysis of covariance (ANCOVA), after the information, a statistically significant difference was found in the personal control, concern, coherence subgroups in the video group compared to the control group (p<0.001, p=0.002, p<0.001, respectively). According to the likert scale, the satisfaction level of the patients in the video group was significantly higher compared to the control group (p<0.001).Conclusion It has been shown for the first time in the literature that visual and auditory information is provided by watching video information about osteoarthritis with an electronic guide. It could be ensured that the patients' control, concern, knowledge, and satisfaction levels could be improved via this application.
Keywords: Knee osteoarthritis; Brief illness perception questionnaire (B-IPQ); Illness perception; Patient satisfaction; Visual and auditory information